East of Modernity: Silent Croatian City Films - Tomić, Janica (2010)
Parallels between "modern", "urban" and "cinematic" experience present a common interpretative frame within the field of silent cinema studies, with paradigmatic examples derrived from the corpus of 'city films', esp. early urban travelogues. The interest behind this paper is to see how that paradigm functions when applied to silent films portraying Croatian cities, made on the periphery of cinematic and wider practices of modernity (or even on the verges of the "pre- or antimodern" imaginary space of the Balkans). The material studied are the silent non-fiction films featuring cities of Zagreb, Split and Dubrovnik, catalogued by the Croatian Film Archive (1911–1940).